Implementation Of Gendhis Canteen Service Standards To Improve Employee Satisfaction In Semarang Hotel - Cut Aisha Febriani; Emik Rahayu (FKIP, Universitas Palangka Raya, 2023)
The canteen is one of the most important parts because it is the main support for employee consumption. They play an important role in providing official food to employees in hotels. The importance of the quality and taste provided is very influential for the satisfaction and comfort of all employees. In providing services, the canteen must serve optimally so that the service will be well received without any dissatisfaction. Data collection methods were collected in 4 ways, namely literature study, observation, interviews, and documentation studies in order to obtain accurate data regarding the satisfaction of canteen staff towards employees. The results obtained from this study are that employees are still dissatisfied with the variety of food menus on weekends. Meanwhile, on weekdays, the variation of the food menu is quite satisfying. A company is said to be successful if employee satisfaction can be guaranteed, and the presence of inhibiting and supporting factors is one of the factors that can be a success of a company or not in its application. The results of this study are that increasing employee satisfaction with canteen services in a company greatly influences the welfare and satisfaction of employees in the company, so it is important for the human resources department to prepare all the facilities needed by employees and also provide excellent service to all employees.